Restrictions of Health Service in Doctor Private Practice During the Covid-19 Pandemic - Muhammad Joni Ardi; Intan Sudarmadi; Dian Sari Pratiwi; Mokhamad Khoirul Huda (Indian Journal of Forensic Medicine & Toxicology, 2021)
Covid-19 has a huge impact on medical workers’ existence. They are at the forefront of treating Covid-19 patients. The high mortality rate for medical workers, especially doctors, indicates the need to regulate the doctor’s office so that there is no paralysis of health services during the Covid-19 pandemic. Data on the high mortality rate for health workers, especially doctors, need to get more attention. Besides, the ratio of doctors to the population is essential. The increasing number in doctors’ death rates causes doctors’ ratio to the population to decrease and needs to be anticipated by restricting the practice of private doctors. Restriction of services in private doctor’s practice places will cause the quality and quantity of services to decrease. Legal protection is also needed for doctors to limit their services in practice places. The government issued several legal rules. It was Act Number 36 the Year 2014 on Health Workers Article 57 paragraph (4) and from medical professional organizations to manage the restriction of health services in private practice.Covid-19 pandemichas created a policy in restricting the health services in doctor’s private practice, aiming to reduce the impact of deaths on doctors. This is following the Medical Act and Medical Ethics Code.